OP0017 The tnf-alpha-induced MIR-18A activates rheumatoid arthritis synovial fibroblast through a positive feedback loop in NF-KAPPA B signalling. (23rd January 2014) - Trenkmann, M.; Brock, M.; Gay, R.E.; Speich, R.; Michel, B.A.; Gay, S.; Huber, L.C.
Abstract : Background: The miR-17-92 cluster encodes six distinct microRNAs (i.e. miR-17, -18a, -19a, -19b, -20a and -92a) and has been found to be a crucial regulator in the pathogenesis of several diseases, e.g. autoimmune disorders. Rheumatoid arthritis (RA) is a chronic autoimmune disease of the joint in which the resident synovial fibroblast (SF) plays a major role in cartilage degradation and activation of immune cells. Objectives: To study expression and function of the miR-17-92 cluster in activated RASF. Methods: RASF were stimulated with 10ng/ml TNFa. Gene expression was analysed by SYBR Green quantitative real time PCR, Western blot and ELISA. RASF were transfected using Lipofectamin2000 (pre-miRs) or AMAXA Nucleofection (plasmids). Activity of the C13orf25 promoter and NF-kB was measured by reporter gene assay. The TNFAIP3 3'UTR was cloned into pmirGLO and reporter gene assays were carried out in pre-miR-18a-transfected Hek293 cells. The chemoattractive potential of RASF was determined using peripheral blood leukocytes (PBL, isolated by erythrocyte lysis) and conditioned medium (CM) from TNFa-stimulated RASF employed as chemoattractant in a transwell migration assay. Results: The miR-17-92 primary transcript (C13orf25) as well as the mature miRs-18a, -19a, -20a and -92a were significantly induced by TNFa in a time dependent manner with peak induction at 16h of stimulation (1.3- up to 1.7-fold, n=8, p<0.05). This induction was depending on a NF-kB-binding site in the C13orf25 promoter, as assessed by reporter gene assay. Transfection of pre-miRs-18a, -19a, -20a and -92a and stimulation of SF with TNFa revealed increased mRNA levels of MMP1 in miR-18a-transfected cells. Further experiments thus were focused on miR-18a. Pre-miR-18a transfection significantly increased the constitutive (MMP1, IL6, MCP1, RANTES) as well as the TNFa-induced expression (MMP1, IL6, IL8, MCP1, RANTES) of mediators of inflammation and joint destruction at mRNA and protein levels (by 1.9- up to 5.1-fold, n=8, p<0.05). In reporter gene assays, we studied the NF-kB signalling inhibitor TNFAIP3 (A20) as a potential target gene of miR-18a (predicted by www.targetscan.org ). With the TNFAIP3 wt 3'UTR construct, miR-18a repressed luciferase activity which was rescued when using the construct in which the miR-18a seed match had been mutated (n=4, p<0.05), proving that TNFAIP3 is a direct target of miR-18a. In miR-18a-transfected RASF, TNFAIP3 protein expression was decreased by 30±19% (n=7, p<0.05). miR-18a enhanced the constitutive as well as TNFa-induced NF-kB activity in RASF by 1.83±1.25-fold and 1.48±0.43-fold (n=6, p<0.05). Measuring the chemoattractive potential of RASF in a transmigration assay, CM from miR-18a-transfected RASF induced more migration of PBL as compared to CM from scrambled RASF (n=8, p<0.05). Conclusions: In RASF, the miR-17-92 cluster is induced by TNFa via the NF-kB pathway and, by repressing TNFAIP3 miR-18a constitutes a positive regulator of NF-kB signalling. Thus, by enhancing the production of inflammatory cytokines and matrix degrading enzymes, miR-18a aggravates the activated phenotype of RASF. Disclosure of Interest: None Declared